PENGARUH FAKTOR LINGKUNGAN FISIK RUMAH DAN PERILAKU PENDERITA TERHADAP KEJADIAN PENULARAN TUBERCULOSIS PARU DI WILAYAH PUSKESMAS WINDUAJI KABUPATEN BREBES - Luthfi Hidayat Maulana; Moh. Husein Sastranegara; Budi Aji (Universitas Muhammadiyah Semarang, 2017)
Tuberculosis (TB) is still a top health problem in the world. TB causes health problems Millions of people per year, and was ranked as the prayer Into Deaths Top causes of infectious diseases at the World taxable income HIV. One indicator used is the Case Detection Rate (CDR). CDR is the proportion of new patients Basil Hold acid (BTA) were found positive and the treatment on the number of new smear-positive patients,which is estimated in the region. The study aims to describe the physical environmental factors homes (lighting) patients with pulmonary tuberculosis, describing the physical environmental factors house (moisture) patients with pulmonary tuberculosis, describing behavioral factors patient pulmonary tuberculosis and analyze the influence of the physical environment of the home patient pulmonary tuberculosis and behavior of patients with pulmonary tuberculosis together -Same the incidence of transmission in the family. The study used survey method with cross sectional approach, the sample to be studied is the total population, ie all patients with pulmonary tuberculosis family as much as 47 respondents. The analysis is univariate analysis aimed at describing the characteristics of each study variable through frequency distribution table, the physical environment and behavioral factors.Followed by multivariate analysis to determine the effect of physical environmental factors homes pulmonary tuberculosis patients and patients with pulmonary tuberculosis behavior together on the incidence of transmission in the family. The results showed that the respondents lighting of the room against pulmonary tuberculosis transmission in most families is the category of poor lighting as many as 23 home patients (48.9%), good lighting category as many as 20 home patients (42.6%), and excellent lighting category by 4 home patients (8.5%); respondents humidity of the room to the transmission of pulmonary tuberculosis in most families is the category of dry humidity as many as 25 home patients (53.2%), the category of normal humidity as many as 19 home patients (40.4%), and the category of wet moisture as much as 3 home patients (6, 4%); respondent behavior in the transmission of pulmonary tuberculosis in most families is the category of behavior not good by 32 patients (68.1%), and the category of good conduct as many as 16 patients (1.9%); physical environmental factors homes pulmonary tuberculosis patients in the form of humidity is more influential than the physical environmental factors such as lighting homes and pulmonary tuberculosis patient behavior in the transmission of the family. Keywords: physical environmental factors homes, behavioral pulmonary tuberculosis patients, and the incidence of transmission.Tuberculosis (TB) masih merupakan masalah kesehatan utama di dunia. tuberculosis menyebabkan gangguan kesehatan jutaan orang per tahun dan menduduki peringkat ke dua sebagai penyebab utama kematian akibat penyakit menular di dunia setelah HIV. Salah satu indikator yang digunakan adalah Case Detection Rate (CDR). CDR adalah jumlah proporsi pasien baru Basil Tahan Asam (BTA) positif yang ditemukan dan pengobatan terhadap jumlah pasien baru BTA positif, yang diperkirakan dalam wilayah tersebut. Penelitian bertujuan untuk mendiskripsikanfaktor lingkungan fisik rumah (pencahayaan) penderita tuberculosis paru, mendiskripsikan faktor lingkungan fisik rumah (kelembaban) penderita tuberculosis paru, mendiskripsikan faktor perilaku penderita tuberculosis paru dan menganalisis pengaruh faktor lingkungan fisik rumah penderita tuberculosis paru dan perilaku penderita tuberculosis paru secara bersama-sama terhadap kejadian penularannya pada keluarga. Penelitian menggunakan metode survei dengan pendekatan Cross Sectional, sampel yang akan diteliti adalah total populasi, yaitu semua keluarga penderita tuberculosis paru sebanyak 47 responden. Analisis yang digunakan adalah analisis univariat bertujuan untuk mendiskripsikan karakteristik masing-masing variabel penelitian melalui tabel distribusi frekuensi, pada faktor lingkungan fisik dan perilaku. Analisis dilanjutkan dengan multivariat untuk mengetahui pengaruh faktor lingkungan fisik rumah penderita tuberculosis paru dan perilaku penderita tuberculosis paru secara bersama-sama terhadap kejadian penularannya pada keluarga.Hasil penelitian menunjukkan bahwa responden pencahayaan ruangan terhadap penularan tuberculosis paru pada keluarga terbanyak adalah katagori pencahayaan kurang sebanyak 23 rumah penderita (48,9%), katagori pencahayaan baik sebanyak 20 rumah penderita (42,6%), dan katagori pencahayaan sangat baik sebanyak 4 rumah penderita (8,5%); responden kelembaban ruangan terhadap penularan tuberculosis paru pada keluarga terbanyak adalah katagori kelembaban kering sebanyak 25 rumah penderita (53,2%), katagori kelembaban normal sebanyak 19 rumah penderita (40,4%), dan katagori kelembaban basah sebanyak 3 rumah penderita (6,4%); responden perilaku terhadap penularan tuberculosis paru pada keluarga terbanyak adalah katagori perilaku kurang baik sebanyak 32 penderita (68,1%), dan katagori perilaku baik sebanyak 16 penderita (1,9%); faktor lingkungan fisik rumah penderita tuberculosis paru berupa kelembaban lebih berpengaruh dibandingkan dengan faktor lingkungan fisik rumah berupa pencahayaan dan perilaku penderita tuberculosis paru terhadap penularan pada keluarganya. Kata kunci: faktor lingkungan fisik rumah, perilaku penderita tuberculosis paru, dan kejadian penularan.